Geology and phosphate deposits of the Permian rocks in central western Montana - Swanson, Roger Warren, 1914- (Geological Survey professional paper, 1973)
Descriptions of Permian rocks and of structure of enclosing rocks at north end of western phosphate field, with measured sections, chemical analyses, and phosphate resource tables.